SOSIALISASI PENYAKIT TIDAK MENULAR DI DESA PEMATANG PANJANG - Diba, Farah; Angelina Novryance Tarapang; Mulidya, Mulidya; Revani Indahtiana; Alfina Raudhoh; Maulida Hardianti; Nurus Sahliah; Ihza Nur Alfaz; Muhammad Fadhilah Muchlis; Saman Abdurrahman (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Kuliah Kerja Nyata (KKN) Membangun Desa Merdeka Belajar 2024" program requires students to apply their knowledge and skills in ways that benefit the community, with the aim of empowering the community and addressing various issues, including low awareness of non-communicable diseases (NCDs). One of the initiatives carried out is the "Protect Yourself" campaign in Pematang Panjang Village, South Kalimantan, which focuses on the prevention of diabetes and obesity. This study aims to evaluate the effectiveness of the "Protect Yourself" campaign in increasing community knowledge and awareness about NCDs, particularly diabetes and obesity, as well as encouraging behavioral changes towards a healthy lifestyle. Through a comprehensive educational approach, including outreach, leaflet distribution, and interactive discussions, the program succeeded in shifting community behavior towards a healthier lifestyle. Close collaboration between students, healthcare workers, and the local community was key to the program's success. The study results indicate that such programs have great potential in preventing NCDs and improving the quality of life for communities, and could serve as a model for similar programs in other regions.